Kill your darlings : a novel - Swanson, Peter, 1968- (William Morrow, an imprint of HarperCollins Publishers, 2025)
"From the New York Times bestselling author of The Kind Worth Killing and Eight Perfect Murders comes an inventive, utterly propulsive murder-mystery in reverse, tracing a marriage back in time to uncover the dark secret at its heart"--